Surface And Interface Phonon Polariton Characteristics Of Wurtzite ZnO-Based Semiconductor By Infrared Attenuated Total Reflection Spectroscopy - Lee, Sai Cheong (2011)
Studies of surface phonon polariton (SPP) characteristics of wurtzite zinc oxide (ZnO) based semiconductors were reported. Attention was paid on the investigations of the SPP and also the interface phonon polariton (IPP) modes in the ZnO heterostructure systems. For comparison, the SPP mode in the bulk ZnO crystal was also investigated. The early effort started with the derivation of the surface polariton (SP) dispersion relations for wurtzite based multilayer systems. The obtained formulations were applied to investigate the dispersion properties of the SPP and IPP modes in the bulk ZnO crystal, ZnO thin film on 6H-SiC substrate, and ZnO/GaN heterostructure on 6H-SiC substrate.